A Survey of Pre-Service English Teachers’ Reading Habits of English Text - Alan Jaelani; Fadia Holisah (Journal of English Language Learning, 2021)
Reading should become a habit for pre-service English teachers. The habit gives significant contribution in both academic and teaching performance. The purpose of this study was to determine the habit of reading English texts for pre-service English teachers. Data was collected through surveys and validation interviews. Questionnaires were distributed to 42 students of English Education at a university in Bogor, West Java using random sampling technique. This study found that the pre-service English teachers’ reading habits of English texts are not in the good category. Based on data analysis, it can be said that they have been reading English texts for more than 12 years. However, it turned out that during more than that period they were not used to reading well and some of them had expressed not having a good habit of reading English texts. This is because they do not read English texts regularly; they tend to read Indonesian texts more often. Some obstacles were identified in reading English texts, such as not being used to reading for a long time, and lack of vocabulary. On the other hand, they have a goal in reading, one of which is to increase their knowledge and English skills. This goal can be achieved by reading English texts regularly. Their plan is to read English texts regularly and ensure positive beliefs that are motivated by themselves, for the goals they want to achieve.